The correlation of muscle biopsy scores with the clinical variables in idiopathic inflammatory myopathies - Suparaporn Wangkaew (2018)
© Wangkaew et al.; Licensee Bentham Open. Objectives: To compare the muscle pathology findings among subgroups of idiopathic inflammatory myopathies (IIM) patients, and to determine the correlations of muscle biopsy scores with muscle power and creatine kinase (CK). Methods: The medical records of IIM patients consisting of the demographic data, clinical parameters and laboratory conducted were retrospectively reviewed. Their initial muscle biopsies were reviewed, and four domains were scored: inflammation, vascular, muscle, and connective tissue. Results: Ninety-five IIM patients (28 patients with idiopathic polymyositis (PM) 9 idiopathic dermatomyositis (DM), 5 DM associated with malignancy, and 53 PM/DM associated with connective tissue disease) with median (IQR: Q1, Q3) disease duration of 1.2 (0.5, 3.1) months were included. No significant differences in initial muscle pathology findings and muscle pathology score among the subgroups were found. Muscle degeneration and endomysial fibrosis scores were negatively correlated with muscle power (r=-0.23 and-0.24, respectively, p<0.05) and positively correlated with CK (r=0.27 and 0.39, respectively, p<0.01). No significant correlation was detected either inflammation or vasculitis scores with muscle power and CK levels. Conclusion: In this study, muscle biopsy cannot be used to differentiate among subgroups of IIM patients. In addition, we found only modest correlation of muscle biopsy scores with muscle power and CK. Further study is necessary to confirm our findings.